A survey of Mysida from the Lizard Island area, Great Barrier Reef, Australia, Subfamily Siriellinae (Crustacea, Mysida, Mysidae) - Talbot, M. Suzette (Zootaxa, 2009)
Ten species of Siriellinae mysids including Siriella lacertilis sp. nov., and one Rhopalophthalminae mysid are reported from the Lizard Island area of the Great Barrier Reef, Australia.